First insights on the molybdenum-copper Bled M'Dena complex (Eglab massif, Algeria). (March 2017) - Lagraa, Karima; Salvi, Stefano; Béziat, Didier; Debat, Pierre; Kolli, Omar
Abstract: Molybdenum-Copper showings in the Eglab massif (eastern part of the Reguibat rise of Algeria), are found in quartz-monzodiorite and granodiorite of the Bled M'Dena complex, a Paleoproterozoic circular structure of ∼5 km in diameter, comprising volcanic and intrusive suites. The latter consist of quartz-diorite, quartz-monzodiorite and granodiorite with a metaluminous normative composition. They display an "adakitic character" with moderate light rare-earth element (LREE) enrichment, minor Eu anomalies, high Sr/Y ratio and low Yb concentration, suggestive of a hydrous, arc magma of volcanic-arc affinity. The mineralization occurs mostly in quartz + molybdenite + chalcopyrite stockwork veins marked by widespread propylitic alteration along the selvages. Molybdenite and chalcopyrite are commonly associated with calcite, which precipitated at relatively late stages of the hydrothermal alteration. Fluid inclusions related to the mineralization stage, range from aqueous to aqueous-carbonic to solid bearing. The latter inclusions have the highest homogenization temperature (up to ∼400 °C), are salt saturated, and commonly contain molybdenite and/or chalcopyrite crystals. The petrology and geochemistry of the host rocks, the style of the hydrothermal alteration, the ore mineral associations, and the characteristics of the fluid inclusions, are all coherent in indicating that the Bled M'Dena represents a Paleoproterozoic porphyry style Mo mineralization, which is far unreported in the African continent. Highlights: First study of porphyry molybdenum-copper mineralization in Algeria and Africa of Paleoproterozoic age. New geological data on the relationship between intrusion and mineralization. The presence of molybdenite as possible daughter minerals is quite exceptional and only rarely observed.